Pengaruh Fasilitas dan Harga Terhadap Keputusan Berkunjung ke Kebun Binatang Bandung - Sendy Sully; Ayu Yudiani Lestari (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the influence of facilities and price on visiting decisions at Bandung Zoo as an urban educational tourism destination. A quantitative approach with an explanatory design was employed to test causal relationships among variables through data collection using structured questionnaires administered to 100 respondents who had previously visited the destination, selected using purposive sampling. The research instruments were validated and tested for reliability prior to analysis. Data were analyzed using multiple linear regression, Pearson correlation analysis, partial tests (t-test), and a simultaneous test (F-test). The results indicate that, partially, price has a statistically significant effect on visiting decisions, while facilities show a positive but statistically insignificant effect. Nevertheless, the simultaneous test confirms that facilities and price jointly exert a significant influence on visiting decisions, with the model demonstrating a substantial explanatory power. These findings suggest that visiting decisions are shaped through a holistic value evaluation process, in which price serves as the primary determinant in visitors’ considerations, whereas facilities function as a supporting element that enhances the overall experience and reinforces the perceived value of the destinationz.